Analysis of NDVI Changes and their Relationship with LST in Khas Kunar, Nurgal, and Chawkay Districts - Ehsas, Taibullah; Khamosh , Ikramullah; Khaksar , Mohammad Rahim (Journal of Natural Sciences – Kabul University, 2026)
This study examines changes in vegetation cover (NDVI) and its relationship with land surface temperature (LST) in the Khas Kunar, Nur Gul, and Sawki districts of Kunar province from 2001 to 2024. Vegetation cover and land surface temperature are key indicators of environmental and climate change. Using Remote Sensing (RS) and Geographic Information System (GIS), Landsat satellite images were analyzed to extract NDVI and LST values for 2001, 2013, and 2024. The results show a decline in vegetation cover mainly due to deforestation, agricultural expansion, and urbanization. In areas with reduced vegetation, LST has generally increased, demonstrating an inverse relationship between NDVI and LST. However, some areas experienced slight decreases in temperature between 2013 and 2024, possibly due to environmental conditions or conservation efforts. The study highlights the need for sustainable land management, reforestation, and the development of urban green spaces to reduce rising temperatures and environmental degradation. These findings offer policymakers and ecological planners in the region helpful guidance.